2020
DOI: 10.1186/s13213-020-01565-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different temperature profiles on simultaneous yeast and bacteria fermentation

Abstract: Purpose: The role of fermentation temperature was studied for its impact on the evolution of malolactic fermentation performed by simultaneous inoculum of yeast and bacteria in grape must. Results were discussed considering the different fermentative kinetics and the composition of obtained wines. Methods: Two strains of bacteria belonging to the O. oeni and L. plantarum species were inoculated 24 h after the beginning of the alcoholic fermentation in 2 grape musts having different acidic and sugar profiles. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…to degrade the malic acid and potentially enhanced acetic acid production. These findings have been recently confirmed by Guzzon and coworkers [58]. They showed that the L. plantarum strain more efficiently carried out the MLF compared to O. oeni, since the latter species was inhibited by a high fermentation temperature with subsequent incomplete malic acid degradation.…”
Section: Impact Of Wine Environment On Lab Metabolismssupporting
confidence: 60%
“…to degrade the malic acid and potentially enhanced acetic acid production. These findings have been recently confirmed by Guzzon and coworkers [58]. They showed that the L. plantarum strain more efficiently carried out the MLF compared to O. oeni, since the latter species was inhibited by a high fermentation temperature with subsequent incomplete malic acid degradation.…”
Section: Impact Of Wine Environment On Lab Metabolismssupporting
confidence: 60%
“…The derivation of a parametric mathematical model of the fermentation process, which also describes the influence of temperature changes on the time course of concentrations of microorganisms, substrate, and fermentation product, is a relatively new field. Although there are many studies showing the influence of temperature on the fermentation processes of different species, these are limited mainly to the observation and numerical evaluation of the influence of different (constant) temperatures on the course of the fermentation process and do not result in deriving a parametric mathematical model [15][16][17].…”
Section: Related Work and Literature Reviewmentioning
confidence: 99%
“…Yeasts and Gram-positive lactic acid bacteria (LAB) are important drivers of the alcoholic and malolactic fermentations, as reviewed by Capozzi et al (2021) [17]. The effect of these organisms during fermentation depends on interspecific interactions [18][19][20], the fermentation temperature [20] and wine chemical parameters such as pH nutrient and oxygen availability [21][22][23][24][25]. Non-Saccharomyces yeasts are often referred to in the context of incomplete or sluggish fermentations and undesirable off-flavors [21,26].…”
Section: Introductionmentioning
confidence: 99%